Accelerating Diffusion‐Ordered NMR Spectroscopy by Joint Sparse Sampling of Diffusion and Time Dimensions. (24th April 2014) - Urbańczyk, Mateusz; Koźmiński, Wiktor; Kazimierczuk, Krzysztof
Abstract: Diffusion‐ordered multidimensional NMR spectroscopy is a valuable technique for the analysis of complex chemical mixtures. However, this method is very time‐consuming because of the costly sampling of a multidimensional signal. Various sparse sampling techniques have been proposed to accelerate such measurements, but they have always been limited to frequency dimensions of NMR spectra. It is now revealed how sparse sampling can be extended to diffusion dimensions. Abstract : Diffusionsgeordnete mehrdimensionale NMR‐Spektroskopie ist eine wertvolle Methode zur Analyse von komplexen Mischungen, der Zeitaufwand für ein mehrdimensionales Signal kann jedoch sehr groß sein. Stichprobenverfahren können die Messung beschleunigen, aber diese waren bislang auf Frequenzdimensionen von NMR‐Spektren beschränkt. Die Anwendung eines Stichprobenverfahrens für Diffusionsdimensionen wurde jetzt entwickelt.